2016
DOI: 10.1016/j.jaci.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new locus at 16q12 associated with time to asthma onset

Abstract: Background Asthma is a heterogeneous disease in which age of onset plays an important role. Objective We sought to identify the genetic variants associated with time to asthma onset (TAO). Methods We conducted a large-scale meta-analysis of 9 genome-wide association studies of TAO (total of 5462 asthmatic patients with a broad range of age of asthma onset and 8424 control subjects of European ancestry) performed by using survival analysis techniques. Results We detected 5 regions associated with TAO at the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 58 publications
6
32
0
Order By: Relevance
“…Despite NOD1, NOD2, or RIP2 not being generally regarded as susceptibility genes for allergic or asthmatic disease, a number of reports suggest an association between polymorphisms in NOD1, NOD2, and RIP2 genes and allergic or asthmatic status . In addition, other studies have reported up‐regulation of these proteins in the setting of allergy or asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Despite NOD1, NOD2, or RIP2 not being generally regarded as susceptibility genes for allergic or asthmatic disease, a number of reports suggest an association between polymorphisms in NOD1, NOD2, and RIP2 genes and allergic or asthmatic status . In addition, other studies have reported up‐regulation of these proteins in the setting of allergy or asthma.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis, which to our knowledge has not been formally tested to date, is supported by the observations that asthma risk alleles are enriched among individuals with early-onset disease. [14][15][16] Moreover, it has been shown that the efficacy of novel anti-cytokine asthma therapies, such as those involving anti-IL-5 17 and the anti-IL-5Ra, 18 is greater in adult-onset disease, again pointing to age-of-onset-dependent disease mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of time‐to‐asthma onset phenotype requires to specify the event (here, asthma occurrence) and the time to event. Information on occurrence of asthma was based on report of doctor's diagnosis and/or on standardized questionnaires, as used in previous GWAS . Childhood asthma was defined as having asthma at or before 16 years of age.…”
Section: Methodsmentioning
confidence: 47%
“…Therefore, similar to the previously reported heterogeneity of SNP effect on asthma risk according to age of onset of asthma, the SNP‐smoke exposure interactions may differ between childhood‐onset and later‐onset asthma and may vary according to time of exposure. Only two GWAS have considered either age of asthma onset in asthmatic children or time‐to‐asthma onset (TAO) in asthmatic and non‐asthmatic subjects and have led to the discovery of new asthma loci, but no GWIS has yet taken into account the time‐to‐asthma onset.…”
Section: Introductionmentioning
confidence: 99%